The use of out-of-plane high Z patient shielding for fetal dose reduction in computed tomography: Literature review and comparison with Monte-Carlo calculations of an alternative optimisation technique. (April 2018) - Ryckx, Nick; Sans-Merce, Marta; Schmidt, Sabine; Poletti, Pierre-Alexandre; Verdun, Francis R.
Highlights: A literature review on patient uterus dose reduction by high Z drapes was performed. MC simulations for optimised protocols were proposed for efficiency comparison. Current CT technical have rendered the need for high Z garments obsolete. Abstract: When performing CT examinations on pregnant patients, great effort should be dedicated towards optimising the exposure of the mother and the conceptus. For this purpose, many radiology departments use high-Z garments to be wrapped around the patient's lower abdomen for out-of-plane organ shielding to protect the fetus. To assess their current protection efficiency, we performed a literature review and compared the efficiencies mentioned in the literature to Monte-Carlo calculations of CT protocols for which the overall scan length was reduced. We found 11 relevant articles, all of them reporting uterus exposure due to CT imaging performed for exclusion of pulmonary embolism, one of the leading causes of peripartum deaths in western countries. Uterus doses ranged between 60 and 660 µGy per examination, and relative dose reductions to the uterus due to high-Z garments were between 20 and 56%. Calculations showed that reducing the scan length by one to three centimetres could potentially reduce uterus dose up to 24% for chest imaging, and even 47% for upper abdominal imaging. These dose reductions were in the order of those achieved by high-Z garments. However, using the latter may negatively influence the diagnostic image quality and even interfere with the automatic exposure control system thus increasing patient dose if positioned in the primary beam, for example in the overranging length in helical acquisition. We conclude that efforts should be concentrated on positioning the patient correctly in the gantry and optimising protocol parameters, rather than using high-Z garments for out-of-plane uterus shielding.